2019
DOI: 10.1002/ejic.201900640
|View full text |Cite
|
Sign up to set email alerts
|

Multidentate Pyridyl‐Aminophosphinite and Pyridyl‐Phosphoramidite Ruthenium(II) Complexes: Synthesis, Structure and Application as Levulinic Acid Hydrogenation Pre‐Catalysts

Abstract: Novel multidentate pyridyl‐aminophosphinite (L1) and pyridyl‐phosphoramidite (L2) ligands of N^P^P^N‐donor system have been synthesized via a series of simple steps. The ligands are symmetrical and as a result, their reactions with [Ru(p‐cymene)Cl2]2 and [Ru(benzene)Cl2]2 lead to the formation of four monodentate bimetallic complexes (1–4) that retain the symmetry of the ligands. Meso and racemic mixtures (rac) of bidentate bimetallic complexes 5–8 were formed from the monodentate complexes through coordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Starting compounds L 1-3 and 1 were prepared according to the literature. [41][42][43] SnCl2, GaCl3 and Sn(OTf)2 were purchased from Sigma Aldrich and used as received. L-lactide was purchased from Sigma-Aldrich and recrystallized from toluene before use.…”
Section: General Considerationmentioning
confidence: 99%
“…Starting compounds L 1-3 and 1 were prepared according to the literature. [41][42][43] SnCl2, GaCl3 and Sn(OTf)2 were purchased from Sigma Aldrich and used as received. L-lactide was purchased from Sigma-Aldrich and recrystallized from toluene before use.…”
Section: General Considerationmentioning
confidence: 99%
“…Compound HL2 was prepared according to the protocol reported in the literature. 27 2-Formyl-6-methoxypyridine (2.74 g, 20 mmol), ethylenediamine (0.60 g, 10 mmol), and MgSO 4 (1 g) were mixed in THF. The reaction mixture was stirred at 50 °C for 4 h. After that, all insoluble materials were filtered off and the THF filtrate was evaporated to dryness.…”
Section: Synthesis Of Dinuclear Copper Complex [Cu 2 Ac 2 O(l1)clo 4 ...mentioning
confidence: 99%
“…37 Makhubela et al reported a dinuclear Ru complex having multidentate pyridyl-aminophosphinite and pyridyl-phosphoramidite ligands ( 12 in Scheme 1) for the transfer hydrogenation of LA using formic acid as a hydrogen source at 120 °C under neat conditions and observed complete conversion of LA in 8 h with a TOF of 123 h −1 . 38 Wildeman et al used a η 4 -(2,3,4,5-tetraphenylcyclopentadienone)-Ru(CO) 3 complex ( 13 in Scheme 1) for LA to GVL transformation under solvent free conditions at 100 °C and 50 bar H 2 pressure and observed a TOF of 144 h −1 . 39 More recently, Hou et al tested a ruthenium hydride complex ( 14 in Scheme 1) for solvent assisted hydrogenation of methyl levulinate to GVL at 100 °C and 10 bar H 2 pressure.…”
Section: Introductionmentioning
confidence: 99%